CD36 Mediated Fatty Acid-Induced Podocyte Apoptosis via Oxidative Stress - Hua, Wei; Huang, Hui-zhe; Tan, Lan-ting; Wan, Jiang-min; Gui, Hai-bo; Zhao, Liang; Ruan, Xiong-zhong; Chen, Xue-mei; Du, Xiao-gang (PloS one, 2015)
Hyperlipidemia-induced apoptosis mediated by fatty acid translocase CD36 is associated with increased uptake of ox-LDL or fatty acid in macrophages, hepatocytes and proximal tubular epithelial cells, leading to atherosclerosis, liver damage and fibrosis in obese patients, and diabetic nephropathy (DN), respectively. However, the specific role of CD36 in podocyte apoptosis in DN with hyperlipidemia remains poorly investigated. The expression of CD36 was measured in paraffin-embedded kidney tissue samples (Ctr = 18, DN = 20) by immunohistochemistry and immunofluorescence staining. We cultured conditionally immortalized mouse podocytes (MPC5) and treated cells with palmitic acid, and measured CD36 expression by real-time PCR, Western blot analysis and immunofluorescence; lipid uptake by Oil red O staining and BODIPY staining; apoptosis by flow cytometry assay, TUNEL assay and Western blot analysis; and ROS production by DCFH-DA fluorescence staining. All statistical analyses were performed using SPSS 21.0 statistical software. CD36 expression was increased in kidney tissue from DN patients with hyperlipidemia. Palmitic acid upregulated CD36 expression and promoted its translocation from cytoplasm to plasma membrane in podocytes. Furthermore, palmitic acid increased lipid uptake, ROS production and apoptosis in podocytes, Sulfo-N-succinimidyloleate (SSO), the specific inhibitor of the fatty acid binding site on CD36, decreased palmitic acid-induced fatty acid accumulation, ROS production, and apoptosis in podocytes. Antioxidant 4-hydroxy-2,2,6,6- tetramethylpiperidine -1-oxyl (tempol) inhibited the overproduction of ROS and apoptosis in podocytes induced by palmitic acid. CD36 mediated fatty acid-induced podocyte apoptosis via oxidative stress might participate in the process of DN.